Integrated View of Formaldehyde in Lung Toxicity: Molecular Mechanisms, Cellular Aberrations and Pathological Considerations - Soheir E. Kotob (Journal of Global Pharma Technology, 2020)
Formaldehyde (FA) is an indoor and occupational pollutant, with marked carcinogenic impact on the airways. The current investigation was initiated to determine the molecular, immunohistochemical and histopathological alterations in lung tissue of rats subjected to FA inhalation and to provide new reliable biomarkers of the hazardous insults of FA on the lung. Adult female Wistar rats were assigned into five groups; (1): negative control; (2): 10 ppm FA inhalation for 15 days; (3): 20 ppm FA inhalation for 15 days; (4): 10 ppm FA inhalation for 30 days and (5): 20 ppm FA inhalation for 30 days. After the experimental periods; rats were killed and lung tissues were harvested and prepared for molecular genetics, immunohistochemical and histopathological procedures. Molecular genetic results indicated significant overexpression in pulmonary Cyp2c6 gene in the group of rats submitted to FA inhalation (20 ppm) for 30 days. The expression level of pulmonary Bhmt gene showed significant upregulation in the groups of rats inhaled 10 and 20 ppm FA for 30 days. Pulmonary Mapk12, HLA-A and GsTpi gene expression levels revealed significant over expression in the groups of rats subjected to FA inhalation (10 ppm) for 30 days and (20 ppm) for 15 as well as 30 days. Meanwhile, the level of expression of pulmonary gene HLA-A recorded significant downregulation in the group of rats inhaled FA (10 ppm) for 15 days versus the control counterparts. In addition, immunohistochmical findings denoted positive immunoreactive responses for PCNA and cytochrome c in the lung tissue with different degrees according to the dose and duration of FA exposure. Histopathological description of lung tissue sections of rats underwent FA inhalation revealed various levels of histoarchitectural alterations depending on the dose and time interval of FA subjection. According to the before mentioned data, it seems that extreme FA burden on the lung leads to devastating effects on the molecular level (genotoxicity) and on the cellular level (proliferation and apoptosis). Also, morophological deformation depicted by histopathological investigation indicated the induction of conformational and structural alterations of lung tissue as a consequence of FA inhalation.